Bone age in malnutrition - Kenanoğlu, Abdullah; Pınar, Tuğrul (The Turkish Journal of Pediatrics, 1963)
Bone ages in 104 children with malnutrition were determined according to the Greulich and Pyle atlas, after it had been decided that there was no other disease present which could retard skeletal development. These children were then divided into four groups according to the degree of malnutrition. The averages of the percentages of bone age in every group was calculated and compared to the Greulich and Pyle standards. From these results it was seen that in children with malnutrition, there was retardation of the bone age in accordance with the degree of malnutrition. This retardation was found to be more marked in boys than in girls.